2017
DOI: 10.1001/jamaophthalmol.2017.0837
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Intravitreous Ranibizumab Compared With Panretinal Photocoagulation for Proliferative Diabetic Retinopathy

Abstract: clinical trial results suggest that ranibizumab is a reasonable treatment alternative to panretinal photocoagulation (PRP) when managing proliferative diabetic retinopathy (PDR), with or without concomitant baseline diabetic macular edema (DME). However, ranibizumab injections are costly. Thus, it would be useful to examine the relative cost-effectiveness of these 2 treatment modalities. OBJECTIVE To evaluate incremental cost-effectiveness ratios of 0.5-mg ranibizumab therapy vs PRP for PDR. DESIGN, SETTING, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 17 publications
4
71
0
2
Order By: Relevance
“…This zone-specific phenomenon is supported by a significant correlation between NPIfpz and NVImpz (Fig. 19 Based on our findings, if the ischemia is responsible for the neovascularization at the neighbouring zone, a FA-guided, region-targeted PRP at ischemic retina may be proposed as the first attempt in early and moderate PDR. 18 However, this rule cannot be simply applied to all perfused/non-perfused neighbouring zones in the retina.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This zone-specific phenomenon is supported by a significant correlation between NPIfpz and NVImpz (Fig. 19 Based on our findings, if the ischemia is responsible for the neovascularization at the neighbouring zone, a FA-guided, region-targeted PRP at ischemic retina may be proposed as the first attempt in early and moderate PDR. 18 However, this rule cannot be simply applied to all perfused/non-perfused neighbouring zones in the retina.…”
Section: Discussionsupporting
confidence: 75%
“…Although Protocol S suggests anti-VEGF treatment as an effective alternative of pan-retinal photocoagulation (PRP), PRP is still the mainstay of treatment for PDR. 19 Based on our findings, if the ischemia is responsible for the neovascularization at the neighbouring zone, a FA-guided, region-targeted PRP at ischemic retina may be proposed as the first attempt in early and moderate PDR.…”
Section: Discussionmentioning
confidence: 68%
“…This study used a 12-month recall period for contacts with health and social care services, which is considered reasonable but towards the boundary of recall for patients. 88 For the economic evaluation, we were primarily interested in our health economic analysis on how the cost per change in BCVA compared with the cost per QALY and hence decided to use complete-case analysis where full data were available for these outcome measures. We do not impute costs and, therefore, this left us with 202 participants (this represents 96.7% of the clinical sample included in primary outcome ITT analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the classic studies [1, 2] and recent cost-effectiveness studies [5, 6], PRP remains the standard cost-effective treatment of choice for PDR, reducing the risk of severe visual loss over the long term by 50% [1]. New laser techniques have recently emerged [9, 18, 19] to decrease the side effects associated with PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, those studies concluded that repeated anti-VEGF injections were not inferior and even superior in the CLARITY study to PRP for treating PDR. However, cost-effectiveness studies [5, 6] have reported that intravitreal ranibizumab as monotherapy for PDR incurred an estimated cost of USD 22,576 compared with USD 7,445 for those treated with PRP for only 2 years, among other calculations that concluded that ranibizumab was a non-cost-effective treatment. This is even more critical when assuming the necessity for life-long treatment [6].…”
Section: Introductionmentioning
confidence: 99%